Language Endangerment and Maintenance: Ilwana Language in Tana River County, Kenya - Chishenga, Medza Christine; Ngure , Kenneth (International Journal of Humanity and Social Sciences, 2025)
Whether a minority language can resist language shift despite the prolonged cultural contact with a dominant language remains a significant topic of debate among linguistic scholars globally. This study investigates the vitality of Kiwilwana in Tana River County, Kenya, where the language has coexisted with dominant languages such as the Pokomo, Kiswahili, and Orma for many years. Despite experiencing intense cultural contact with dominant language speakers, Kiwilwana has maintained its vitality in many domains of language use. This paper examines the language use patterns among Ilwana speakers in a multilingual and multiethnic setting, focusing on the domains of language use as critical for intergenerational transmission. Data was collected using a mixed-methods research design, from 73 Ilwana speakers across different age groups. The findings reveal that Kiwilwana is maintained primarily in the home domain, with 77% of respondents using it as their primary language. However, the use of other languages in different domains indicates a potential threat to its long-term survival. The study concludes that while Kiwilwana exhibits resistance to language shift, its maintenance is endangered and requires targeted efforts to ensure its continued vitality.